(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
A 50 years old male patient was admitted with complaints of change in voice for 2 years, dry cough 2 month and difficulty in breathing for 1 month. On examination with fiberoptic laryngoscope, an exophytic lesion covered with whitish plaque involving right vocal cord extending from anterior commissure to right arytenoid region, extending upto the right vestibular area and hanging in the subglottic area was seen. Patient was treated with Microlaryngeal Laser excision and the Histopathology report was suggestive of Verrucous Carcinoma of Larynx. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 208-211